Impact of Modernization of Rani Jamara Kulariya Irrigation System in Kailali District - Risal, Nirbhaya; Dahal, Khet Raj; Parajuli, Ramesh (International Journal on Engineering Technology, 2025)
The modernization of the Rani Jamara Kulariya Irrigation System (RJKIS) in Tikapur, Kailali district, Nepal, has significantly impacted agricultural productivity, water management, and socio-economic conditions in the command area. The study examines the impacts of the modernization of the irrigation system after the completion of the first phase of modernization and the ongoing second phase of modernization which is close to the completion phase. A questionnaire, interviews, and field observation were used to collect data about the pre-modernization position and the recent status of the system. The study reveals an increase in cropping intensity from 193% to 253%, a shift toward diversified crops, and an increase in the annual crop value of NPR 5,660.27 million. Institutional strengthening of the Water User Association (WUA) improved governance and dispute management in the farmer community with affirmative ratings of modernization showing better operational efficiency. Labour shifts created employment opportunities, contributing NPR of 1.47 billion annually. The financial assessment indicates a pay-back period of 8 years, with an Economic Rate of Return (ERR) of 12.96% and a Benefit Cost (B/C) Ratio of 4.63 illustrating the system’s economic sustainability and financial viability. For sustaining the system, farmer training, policy revision, agro-industry promotion, and community participation enhancement are the primary recommendations.